Use of FDA‐Approved Medications: Biologics for Psoriatic Arthritis in Patients at an Urban Outpatient Rheumatology Clinic. Issue 9 (12th September 2019) - Khanna, Ira; Kozicky, Orysia; Fischer, Harry
Abstract : Objective: Psoriatic arthritis (PsA) is an inflammatory arthritis associated with psoriasis that manifests as peripheral arthritis, dactylitis, enthesitis, and spondylitis. Biologics, particularly tumor necrosis factor inhibitors (TNFis) and some interleukin 17 (IL‐17) and interleukin 23 (IL‐23) inhibitors, are the only US Food and Drug Administration (FDA)–approved treatments shown to limit joint damage in clinical trials for PsA. Conventional synthetic disease‐modifying antirheumatic drugs have also been adapted to PsA treatment. Current 2018 American College of Rheumatology (ACR) guidelines regard TNFis as first‐line therapy in treatment‐naïve patients. The aim of this project is to review the prescribing practices for patients with PsA at an urban rheumatology office, with a focus on biologic prescribing. Methods: A retrospective chart review was performed to search for patients seen from June 1, 2017, to June 1, 2018, using International Classification of Diseases, 10th Revision codes for PsA. A log of prescribing practices listed the use of biologics versus oral small molecules (OSMs) (methotrexate, sulfasalazine, leflunomide, and apremilast) across different ages, sex, and disease severity. Results: This study included a total of 97 patients (40 women and 57 men), and 66% were on biologics (60% of women and 70% of men). There was no sex bias in biologic prescribing ( P = 0.59). Use of biologics was highest in the 38 to 57 years age group and lowest in the 78 to 97 years age group, although, statistically, there was no age bias in biologic prescribing ( P = 0.22). Biologics provided superior disease control (84.37%) compared with nonbiologics (66.6%) ( P = 0.0016). OSMs provided slightly better control (69.5%) over apremilast monotherapy (61.5%) ( P = 0.016). Conclusion: There is no age or sex bias in prescribing practices for PsA. In accordance with the ACR, patients with controlled symptoms on OSMs are being appropriately maintained. Although apremilast is allocated as an add‐on therapy, 13.4% of patients were on apremilast monotherapy. This quality improvement project reveals that in most instances, biologics are being appropriately initiated as the primary mode of therapy for patients with PsA at our outpatient practice; however, treatment modifications can be made regarding patients who are managed with apremilast alone.